Developing a Model for the Establishment of Pre-Hospital Emergency Medicine Bases in the Northern Provinces of Iran - Azadeh Ahmadi Dashtiyan; Iravan Masoudi Asl; Leila Riahi; Mahmood Mahmoodi (Farmeconomia: Health Economics and Therapeutic Pathways, 2019)
BACKGROUND: The faster and more accurately Pre-Hospital Emergency Medicine as the first line of care and treatment is done, the less the mortality and disability rates are.